2022
DOI: 10.1002/ppap.202200012
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma for addressing the COVID‐19 pandemic

Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has greatly stressed the global community, exposing vulnerabilities in the supply chains for disinfection materials, personal protective equipment, and medical resources worldwide. Disinfection methods based on cold atmospheric plasma (CAP) technologies offer an intriguing solution to many of these challenges because they are easily deployable and do not require resource‐constrained consumables or reagents needed for conventional decontamination practices. CAP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 123 publications
1
9
0
Order By: Relevance
“…In addition, it has been observed that removing the RONS and allowing only the pass of UV radiation completely removes the ability of NTP to inactivate pathogens . Based on our current and previous results, we hypothesize that the unique combination of RONS produced by the DBD makes the treatment effective due to the simultaneous multitarget activity of NTP-derived RONS …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, it has been observed that removing the RONS and allowing only the pass of UV radiation completely removes the ability of NTP to inactivate pathogens . Based on our current and previous results, we hypothesize that the unique combination of RONS produced by the DBD makes the treatment effective due to the simultaneous multitarget activity of NTP-derived RONS …”
Section: Discussionsupporting
confidence: 55%
“…54 Based on our current and previous results, 48 we hypothesize that the unique combination of RONS produced by the DBD makes the treatment effective due to the simultaneous multitarget activity of NTP-derived RONS. 55 Regarding the role of temperature in viral inactivation, it is known that coronaviruses and coxsackieviruses require temperatures of around 50 °C to reduce their infectivity. 56,57 Therefore, the virucidal activity of our NTP source was not due to thermal damage, as in all cases, the temperature remained below 35 °C.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Cold atmospheric plasma technology is a method that generates a high concentration of H 2 O 2 that causes oxidation of amino acids, nucleic acids, and induces peroxidation of unsaturated fatty acid through interaction with membrane lipids, altering the function of membranes in microorganisms. Chen et al found that cold at-mospheric plasma eliminated SARS-CoV-2 on the surface of living organisms within 180 s [ 37 ]. In addition to its potential benefits in infection control and wound healing, cold atmospheric plasma has also been applied in studies targeting hemostasis control, treatment of skin diseases, immunotherapy, and regenerative medicine [ 37 ].…”
Section: Types Of Oral Antiseptics Against Sars-cov-2mentioning
confidence: 99%
“…Chen et al found that cold at-mospheric plasma eliminated SARS-CoV-2 on the surface of living organisms within 180 s [ 37 ]. In addition to its potential benefits in infection control and wound healing, cold atmospheric plasma has also been applied in studies targeting hemostasis control, treatment of skin diseases, immunotherapy, and regenerative medicine [ 37 ]. On the other hand, one of the first strategies implemented to prevent SARS-CoV-2 transmission during dental procedures was the use of a preoperative rinse consisting of 1% hydrogen peroxide solution to reduce viral load, due to the vulnerability of the virus to oxidation [ 3 ].…”
Section: Types Of Oral Antiseptics Against Sars-cov-2mentioning
confidence: 99%
“…In the realm of biomedical applications, cold atmospheric plasma (CAP) has been employed to combat the COVID-19 pandemic by eliminating the virus [ 20 , 21 , 22 , 23 , 24 , 25 ]. The transmission of COVID-19 occurs through respiratory droplets originating from infected individuals’ coughs and sneezes.…”
Section: Introductionmentioning
confidence: 99%